Evaluation of Medicinal uses, Phytochemistry and Biological Activities of Adenia gummifera (Harv.) Harms - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Adenia gummifera (Harv.) Harms is a climber or liane widely used as traditional medicine throughout its distributional range in tropical Africa. Adenia gummifera occurs naturally in the Democratic Republic of Congo (DRC), Eswatini, Ethiopia, Kenya, Malawi, Mozambique, Seychelles, Somalia, South Africa, Tanzania, Uganda, Zambia and Zimbabwe. This study is aimed at providing a critical review of the medicinal uses, phytochemistry and biological activities of A. gummifera. Documented information on the medicinal uses, phytochemistry and biological activities of A. gummifera was collected from several online sources, which included Scopus, Google Scholar, PubMed and Science Direct. Additional information was gathered from pre-electronic sources such as book chapters, books, journal articles and scientific publications sourced from the university library. This study showed that the species is widely used as an emetic and a protective charm, and, as traditional medicine for infertility, sexually transmitted infections, gastro-intestinal infections, leprosy, respiratory infections, malaria and menstrual problems. Phytochemical compounds identified from the species include polyacetylenic diepoxide, alkaloids, flavonoids, flavonol, modeccin, proanthocyanidins, tetraphyllin, phenolics, polyphenol and tannins. Pharmacological research revealed that A. gummifera extracts and compounds isolated from the species have antibacterial, antifungal, acetylcholinesterase inhibitory (AChEI), anaesthetic, antioxidant, antiplasmodial and cytotoxicity activities. Future research on A. gummifera should focus on detailed phytochemical evaluations including toxicological, in vivo and clinical studies to corroborate the traditional medical applications of the species.